ANALISIS SUMBER DAN JENIS PEMBIAYAAN PENDIDIKAN DI INDONESIA - Sonny Muhammad Ikhsan Mangkuwi; Vesfi Yulia; Walidaini Walidaini; Wan War Safitria (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study investigates the sources and forms of education funding in Indonesia using a systematic literature review approach based on the PRISMA model. Twenty-five journal publications from 2013 to 2023 relevant to the research topic were analysed to collect data for the literature investigation. Twelve of the twenty-five articles were found to be relevant and were reviewed. Ten articles, according to the analysis findings, discuss the sources and forms of education funding in Indonesia with an emphasis on the effectiveness of education fund management. On the other hand, two articles were considered less relevant as they discussed the basics of funding and financing planning. The definitions and concepts of school finance, its legal basis, various forms, and sources—including government funds, private donations, and parental contributions—are all discussed in this paper. Planning, accounting, and evaluation are all part of the education finance cycle, which ensures that financial resources are used effectively and efficiently. This study offers a comprehensive overview of education financing in Indonesia, emphasising the important role of the government, society, and educational institutions in contributing funds to support the sustainability and quality of education in the long term.